2007
DOI: 10.2310/6670.2007.00046
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Eversion Carotid Endarterectomy for Carotid Atherosclerosis: Single-Center Experience with 5,034 Patients

Abstract: The aim of this article is to review our experience in surgical treatment of carotid atherosclerosis using eversion carotid endarterectomy (ECEA) in 5,034 patients, with particular attention to temporal changes in patients' characteristics, diagnostic approach, surgical technique, medical therapy, and outcome in the early (group A, 1991-1997) versus late (group B 1998-2004) period of ECEA. From January 1991 to December 2004, 5,034 primary ECEAs were performed for high-grade carotid stenosis. Patients treated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…This makes the suturing easier and more comfortable for the surgeon. With the confidence of a shorter clamp time, the need for a shunt may be dramatically reduced, as evidenced by the extremely low usage reported by Radak et al 69 and Darling and colleagues. 24 Many surgeons have reported clamp times close to 10 minutes.…”
Section: Clamp Times and Cerebral Ischemiamentioning
confidence: 82%
See 2 more Smart Citations
“…This makes the suturing easier and more comfortable for the surgeon. With the confidence of a shorter clamp time, the need for a shunt may be dramatically reduced, as evidenced by the extremely low usage reported by Radak et al 69 and Darling and colleagues. 24 Many surgeons have reported clamp times close to 10 minutes.…”
Section: Clamp Times and Cerebral Ischemiamentioning
confidence: 82%
“…Radak and associates 69 reported clamp times averaging 12.4 minutes in the latter part of their series of more than 5000 patients, and 14.5 minutes in the first group. The same authors reported significantly shorter clamp times with eversion than with conventional CE (13.5 and 19.9 minutes, respectively) in their earlier prospective study.…”
Section: Clamp Times and Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…If there are atherosclerotic changes associated with CAs in the same procedure eversion carotide endarterectomy can be done 21,31,35 . Similarly, Radak et al 37 reported low total mortality rate after endarterectomy procedures of carotid artery 37 . Similarly, Radak et al 37 reported low total mortality rate after endarterectomy procedures of carotid artery 37 .…”
Section: Treatment Of Carotid Abnormalities: Indications and Surgicalmentioning
confidence: 88%
“…Carotid endarterectomy reduces the risk of subsequent stroke in patients with symptomatic stenosis [6][7][8][9][10][11] but there is one neglected fact: the risk of stroke is highest in the first weeks following initial symptoms, which meens that long waiting could be dangerous [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%